Clinically node-negative head and neck mucosal melanoma: An analysis of current treatment guidelines & outcomes. (May 2019) - Torabi, Sina J.; Benchetrit, Liliya; Spock, Todd; Cheraghlou, Shayan; Judson, Benjamin L.
Highlights: Most mucosal melanoma cases are not treated within national guidelines. Head and neck mucosal melanoma carries a poor overall survival. Radiotherapy may be a useful adjuvant therapy. The role of elective neck dissections is unclear. Tumor staging may need to be rethought to create clearer prognostic stages. Abstract: Objectives: To analyze head and neck mucosal melanoma (MM) treatment patterns, and their association with survival, relative to National Comprehensive Cancer Network (NCCN) guidelines. Material & methods: Adult head and neck MM patients with clinically-staged T3/4aN0 disease were identified in a retrospective analysis of the National Cancer Database (2010–2014) and stratified into sinonasal cavity (SN) and oral cavity, oropharynx, larynx, or hypopharynx (non-SN) cohorts. Results: We identified 353 SN and 79 non-SN MM cases. The majority of patients were treated with surgery (SN: 92.4%; non-SN 84.8%), within NCCN guidelines. Treatment within the non-SN MM NCCN recommendation of elective neck dissection (END) was approximately 26.6%. END is not recommended for SN MM and was not performed in 91.5% of cases. Radiotherapy (RT) is recommended in both SN and non-SN MM and was utilized in 63.5% of SN patients and 46.8% of non-SN patients. END was not independently associated with OS compared to surgery alone (SN HR: 1.350 [95% CI: 0.733–2.485]; non-SN HR: 3.460 [95% CI: 0.912–13.125]). RT was independently associated with improved OS in SN MM cases (HR: 0.679 [95% CI: 0.479–0.963]), but not in non-SN MM cases (HR: 0.824 [95% CI: 0.331–2.051]). Conclusion: The majority of patients with head and neck MM are not treated within NCCN guidelines. The use of recommended END in non-SN patients is low. Similarly, adjuvant RT utilization is low. Our analysis shows that while greater use of RT may increase survival rates in this disease, the utility of END is unclear.